2017
DOI: 10.1111/jth.13590
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and pathophysiologic roles of interaction between C‐type lectin‐like receptor 2 and podoplanin: partners from in utero to adulthood

Abstract: Summary A platelet activation receptor, C‐type lectin‐like receptor 2 (CLEC‐2), has been identified as a receptor for a platelet‐activating snake venom, rhodocytin. CLEC‐2 protein is highly expressed in platelets/megakaryocytes, and at lower levels in liver Kupffer cells. Recently, podoplanin has been revealed as an endogenous ligand for CLEC‐2. Podoplanin is expressed in certain types of tumor cells, fibroblastic reticular cells (FRCs) in lymph nodes, kidney podocytes, and lymphatic endothelial cells, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 73 publications
0
93
0
2
Order By: Relevance
“…The exact mechanism underlying the blood-lymphatic vessel separation is still controversially debated. Different hypotheses are discussed, including the "platelet plug theory," the "platelet granule content theory," and the "prevention of backflow at the lymphovenous junction theory" (38). Soluble mediators released from activated platelets, including TGF-␤1 in particular, inhibit the proliferation and migration of lymphatic endothelial cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism underlying the blood-lymphatic vessel separation is still controversially debated. Different hypotheses are discussed, including the "platelet plug theory," the "platelet granule content theory," and the "prevention of backflow at the lymphovenous junction theory" (38). Soluble mediators released from activated platelets, including TGF-␤1 in particular, inhibit the proliferation and migration of lymphatic endothelial cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report, however, attributed Clec-2 on mouse B cells to the acquisition from exogenous sources, for example, by trogocytosis, and showed that Clec-2 on mouse myeloid cells is lost during the entrance of these cells into secondary lymphoid organs (45). The function of CLEC-2 on platelets is well defined as stimulating platelet activation and aggregation (10,24,41). Chimeric receptors composed of the cytoplasmic tail of Clec-2 fused to the transmembrane and extracellular domains of Dectin-1-stimulated phagocytosis and the production of proinflammatory cytokines by mouse neutrophils, but not a respiratory burst (36).…”
Section: Hemitam Receptorsmentioning
confidence: 99%
“…Originally, CLEC-2 was found to act as a receptor of the snake venom rhodocytin (24), with the transmembranous glycoprotein podoplanin later identified as an endogenous cellular ligand of CLEC-2 (24,40). Podoplanin is expressed on multiple cell types such as lymphatic endothelial cells, type I alveolar cells, and keratinocytes but also on some tumor cells (41). In the original report on human CLEC-2 (38), the broad presence of transcripts encoding this protein was noted in bone marrow cells and among peripheral blood mononuclear cells, including myeloid cells such as monocytes, DCs, and granulocytes, and a few NK cell clones, indicating a heterogeneous expression pattern.…”
Section: Hemitam Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that platelets facilitate lung development through the interaction between the platelet activation receptor C-type lectin-like receptor-2 (CLEC-2), and its ligand membrane protein, podoplanin. [115][116][117] CLEC-2 deletion in mouse platelets led to neonatal lethality due to lung malformation and respiratory failure. In the primary alveolar septa of these embryos, α-smooth muscle actin-positive alveolar duct myofibroblasts (adMYFs) were almost absent, which was caused by abnormal differentiation of lung mesothelial cells (luMCs) into adMYFs.…”
Section: Mechanisms Of Fc-independent Immune Thrombocytopeniamentioning
confidence: 99%